Distinct trajectories of athlete development: A retrospective analysis of professional rugby league players - Cupples, B.; O`Connor, D.; Cobley, S. (Journal of Sports Sciences, 2018)
Contemporary models of athlete development (e.g., Development Model of Sport Participation) suggest attainment benefits from early age multi-sport "sampling" behaviour before progressive transition into "invested" single-sport involvement in teenage years compared to intensive early-age specialisation. However, specific examinations of these development patterns across a number of team sports and cultural contexts remains limited. This study involved a large sample of professional Australian Rugby League (RL) players (N = 224) who progressed along the RL system pathways. It defined two contrasting athlete development trajectories based upon initial entry into formal age group representative teams ("Early": U16, U18; "Later": U20+) to compare their developmental participation patterns using the National Rugby League Athlete Development Questionnaire (NRLADQ). Between-Within Analyses of Variance (BW-ANOVA)`s identified interaction effects as the `Later` group reported lower volumes of deliberate practice from 10-20 years, RL-game involvement from 10-20 years, deliberate play from 5-12 years, and a later reduction in other sporting involvement. Group differences in RL-related deliberate practice and play were supported by qualitative descriptions of training at age-categories. Conclusion: RL professional senior elite success level can be attained via early intensified specialised investment and accelerated youth success as well as by a rather decelerated, much less cost-intensive participation pattern.